THE CAUSES AND EFFECTS OF ASUU STRIKE ON ACADEMIC ACTIVITIES OF PUBLIC UNIVERSITY STUDENTS IN NIGERIA (2015-2021) - Njoku, Angelina Chigozie (African Journal of Social and Behavioural Sciences, 2022)
The study examines the major causes and effects of Academic Staff Union of Universities (ASUU) strike on the academic activities of public university students in Nigeria. The paper is qualitative in nature as it utilized secondary sources of data such as articles, textbooks, newspapers and online materials. The findings of the study established that inadequate funding of the universities, non-payment of financial entitlements of academic staff and the imposition of Integrated Payroll and Personnel information system are major causes of ASUU strike. The paper equally uncovered that the effects of ASUU strike on the academic activities of public university students are disruption in academic activities, irregular learning in the universities and discouragement and de-motivation of students in their academics. The paper recommended collaborative action plans by Government, University Management and ASUU towards harmonization and implementation of ASUU demands and adequate funding of the universities; development of good study habit skills, tutorial classes, and self study to reduce the effects of ASUU strike on the academic activities of public university students.